2015
DOI: 10.1186/s40246-015-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Success stories in genomic medicine from resource-limited countries

Abstract: In recent years, the translation of genomic discoveries into mainstream medical practice and public health has gained momentum, facilitated by the advent of new technologies. However, there are often major discrepancies in the pace of implementation of genomic medicine between developed and developing/resource-limited countries. The main reason does not only lie in the limitation of resources but also in the slow pace of adoption of the new findings and the poor understanding of the potential that this new dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 57 publications
0
42
0
3
Order By: Relevance
“…For example, in many European countries and the USA, and as noted above, academic centres are moving towards considerations and implementations of pre‐emptive genotyping . Effort is being made in some other countries as summarized by a report in 2015 . A 2016 study in Singapore has also shown that almost 30% of adverse drug reactions could have been prevented if PGx testing was pre‐emptively administered …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in many European countries and the USA, and as noted above, academic centres are moving towards considerations and implementations of pre‐emptive genotyping . Effort is being made in some other countries as summarized by a report in 2015 . A 2016 study in Singapore has also shown that almost 30% of adverse drug reactions could have been prevented if PGx testing was pre‐emptively administered …”
Section: Discussionmentioning
confidence: 99%
“…Despite these efforts, PGx clinical implementation may still be facing different challenges in different parts of the world . In addition, the majority of the documented efforts are concentrated in the USA and Europe, while not much information is available from other parts of the world, with few exceptions . Therefore, the aim of this study was to administer a modified version of the 2010 survey, in an electronic format and on an international scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human genomics centres in LMIC might include facilities for DNA sequencing (both Sanger and NGS techniques) and for DNA genotyping, complementing the departments focused on specific research topics, such as population genetics and genomics of human diseases 10. In addition to the initial investment for the creation of a human genomics centre (construction or adaptation of buildings, acquisition of high tech equipment and hiring of scientific personnel), it is crucial that novel centres have financial support for their long-term operation.…”
mentioning
confidence: 99%
“…These centres might represent the collaboration of groups from LMIC with previous local experience in human genetics and genomics research 10. These existing local networks could facilitate interactions with clinical centres that have access to the patients and their families.…”
mentioning
confidence: 99%